2011
DOI: 10.1021/jp2027466
|View full text |Cite
|
Sign up to set email alerts
|

Wetting Property of the Edges of Monoatomic Step on Graphite: Frictional-Force Microscopy and ab Initio Quantum Chemical Studies

Abstract: In this work, we present the wetting property of the edges of a monatomic step on graphite. We have used frictional force microscope to experimentally investigate the wetting property of these edges. We have carried out quantum chemical calculations on a model system of nanographene to characterize hydrogen-bonding interactions between water and two different edges of the graphene, namely, the zigzag and arm-chair edges, to explain our experimental results. We have clearly observed two distinct frictional prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…The origin of this resistive force during descending remains controversial [19,21,22,27]. Moreover, the shape of the friction signal during descending reported in the literature also varied drastically-in some papers, the friction profile was a single peak [19,20,22,23,26,27,30], but in some others, the friction profile seemed to be composed of two peaks with a valley between them [20,21,28,29]. For better understanding the origin of the resistance during descending, it is critical to resolve this discrepancy.…”
Section: (A))mentioning
confidence: 99%
See 3 more Smart Citations
“…The origin of this resistive force during descending remains controversial [19,21,22,27]. Moreover, the shape of the friction signal during descending reported in the literature also varied drastically-in some papers, the friction profile was a single peak [19,20,22,23,26,27,30], but in some others, the friction profile seemed to be composed of two peaks with a valley between them [20,21,28,29]. For better understanding the origin of the resistance during descending, it is critical to resolve this discrepancy.…”
Section: (A))mentioning
confidence: 99%
“…This finding implies that the previous Refs. [19,20,22,23,26,27,30], in which the scan resolution was not high enough, might have missed the fine features in the friction response of the single-layer graphene step edge during the step-down scan.…”
Section: (A))mentioning
confidence: 99%
See 2 more Smart Citations
“…26 The trans-edge is more hydrophilic as compared to the overall cis-edge, which has been established both experimentally and theoretically. 27−29 It was theoretically shown that chain of epoxy groups are responsible for oxidative unzipping of GO sheets 22,23,30,31 but none of the studies indicated any preference in generation of cis-edge or trans-edge after reduction A nanoscale graphene sheet has highly hydrophobic faces and slightly polar edges 25,29,32 with trans-edge being more polar.…”
Section: ■ Introductionmentioning
confidence: 99%